(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This article analyzes the illegality of monocratic injunctions issued by the Federal Supreme Court (STF), in violation art. 10 of Law n.º 9.868/1999 and, above all, the unconstitutionality of the violation of the full bench clause provided for in art. 97 of the Federal Constitution. It therefore aims to make a systemic analysis of the monocratic precautionary measures that suspend the validity of a law or normative act and replace, in time and merit, without justification of exceptional legal circumstance, the collegiate decision required by the Constitution, in evident transitional usurpation of the jurisdiction of the plenary. The present research emerged from the fact that most of the precautionary decisions issued by the Supreme Court are made monocratically by its ministers. In spite of the legal provision of the monocratic decision, such a hypothesis should be exceptional in situations in which the immediate suspension of the validity of the contested rule is indispensable for the production of any irreversible effects, due to the general duty of caution of the monocratic judge - without, however, exclude further analysis by the collegiate.